Umbilical cord diameter study on microscopic tissue in gestational diabetes mellitus and its correlation to fresh tissue diameter and fetomaternal parameters - Seema Valsalan E; Jumi Jacob; Akhil P Pushkar; Mahesh Kumar D; Sai Sailesh Kumar Goothy (Asian Journal of Medical Sciences, 2023)
Background: Umbilical cord is the only vital link between the mother and the fetus and is essential for maintaining the fetomaternal exchange of oxygen, nutrients, and waste products. Clinical studies have shown that umbilical cord diameter (UCD) is larger in gestational diabetes mellitus (GDM) and UCD analysis based on microscopic tissue (dry) provides more accurate information. Aims and Objectives: The present study was conducted to measure the UCD using microscopic tissue in GDM and normal cases and ascertain its correlation with fresh tissue (wet) diameter, fetal weight, maternal BMI, and gestational weight gain. Materials and Methods: The study included 111 subjects. They were divided into two groups. Group I consisted of umbilical cords obtained from non-diabetic pregnant women (n=52) and Group II comprised umbilical cords obtained from mothers with GDM (n=59). UCD was measured using Vernier calipers and all the other parameters were assessed through standard methods. Results: UCD in microscopic (P=0.005) and fresh tissues (P=0.0001) was significantly higher in GDM patients. Although microscopic tissue measurements tended to underestimate fresh-tissue measurements of UCD, these measurements had a positive correlation with each other in both groups. UCD also had a statistically significant positive correlation with maternal BMI and a negative correlation with gestational weight gain. Conclusion: UCD in GDM was statistically higher in both microscopic and fresh tissues and thus may be considered for GDM screening. The correlation of wet and dry specimens can also provide useful insights in clinical situations centered around variations in UCD.